Dietitians as agents of change to increase legume consumption: a randomized controlled trial of a behavioral intervention - Ofir, Orit; Stark, Aliza H.; Abu Ahmad, Wiessam; Bar-Zeev, Yael (Frontiers in Nutrition, 2026)
IntroductionHealth and environmental benefits of daily legume consumption are reflected in Israeli Dietary Guidelines. However, legume intake fails to meet recommendations. Dietitians may be effective agents of change for promoting legume consumption. This study evaluates an evidence and theory-based, multi-component, intervention aimed to improve Israeli dietitians’ legume counseling practices, knowledge, attitudes and personal intake.MethodsA randomized controlled trial (May–September 2023) was conducted among dietitians who actively counsel patients. The intervention included a prerecorded webinar followed by small-group workshops and provision of brochures for patients, alongside a professional guide on legume counseling for dietitians. Data regarding legume knowledge, attitudes, counseling practices and personal intake were collected at baseline and 3 months post-intervention. Controls were wait-listed to receive the intervention. The primary outcome was self-reported proportion of patients recommended to consume legumes daily (1–5 Likert scale: (1) none; (2) ≤25%; (3) 26–50%; (4) 51–75%; and (5) 76–100%). A repeated measures mixed-design model, chi-square tests and pairwise odds ratio tests were utilized for the analysis.ResultsOverall, 213 dietitians participated (Intervention: n = 109, Control: n = 104). The proportion of dietitians in the intervention group recommending to 76–100% of their patients to consume legumes daily increased from 32% (baseline) to 51% (follow-up); compared to 25 and 27%, respectively, in the controls. In the repeated measures model, recommending daily legume consumption improved significantly in both the intervention group (3.73 ± 1.1 to 4.28 ± 0.86, p = 0.001) and the control (3.67 ± 0.98 to 3.88 ± 0.92, p = 0.03), with a higher increase in the intervention group (p = 0.014). Knowledge and attitudes improved significantly in the intervention group (p < 0.001) but not for controls, except in the attitude score regarding sustainability (p = 0.026). Personal legume consumption improved significantly only in the intervention group, who had higher odds of increasing legume intake to at least twice a week [OR 2.81 (95%CI: 1.10–8.11)].DiscussionAn online intervention significantly improved dietitians’ knowledge, attitudes, counseling practices regarding legume consumption and personal intake. Utilizing dietitians’ counseling might be a viable approach for promoting consumption of sustainable diets.